2009
DOI: 10.1021/ol900066c
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Carbolithiation Reactions for the Synthesis of 2,4-Disubstituted Tetrahydro-quinolines: Evaluation of TMEDA and (−)-Sparteine as Ligands in the Stereoselectivity † Dedicated to Prof. Josep Font on the occasion of his 70th birthday.

Abstract: The preparation of 4-substituted 2-phenyltetrahydroquinolines from N-alkenylsubstituted 2-iodoanilines via intramolecular carbolithiation reactions has been investigated. The stereochemical outcome of the carbolithiation reactions depends on the nature of organolithium employed to perform the lithium-halogen exchange, the solvent, or the use of additives, for example, TMEDA or chiral bidentated ligands such as (-)-sparteine. Thus, the 2,4-disubstituted tetrahydroquinolines are obtained with moderate diastereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Li (1) t-BuLi/(-)-sparteine 2009 年, Lete 等 [46] 报道了以(-)-sparteine 作为手性 配体, 用邻碘苯胺衍生物 60 进行分子内碳锂化反应研 究, 高立体选择性地合成了 2,4-二取代四氢喹啉化合物 用 Weinreb 酰胺 60c 时使非对映选择性达到最好结果. 2012 年, Lete 等 [31] 研究表明, 未取代烯烃 63a 不会 发生芳基锂环化反应, 而酰胺基的引入有利于在低温下 快速环化, 并以较好收率得到吡咯异喹啉 64b, 但对映 选择性较低(37% ee) (Eq.…”
Section: Phunclassified
“…Li (1) t-BuLi/(-)-sparteine 2009 年, Lete 等 [46] 报道了以(-)-sparteine 作为手性 配体, 用邻碘苯胺衍生物 60 进行分子内碳锂化反应研 究, 高立体选择性地合成了 2,4-二取代四氢喹啉化合物 用 Weinreb 酰胺 60c 时使非对映选择性达到最好结果. 2012 年, Lete 等 [31] 研究表明, 未取代烯烃 63a 不会 发生芳基锂环化反应, 而酰胺基的引入有利于在低温下 快速环化, 并以较好收率得到吡咯异喹啉 64b, 但对映 选择性较低(37% ee) (Eq.…”
Section: Phunclassified
“…Similarly, the intramolecular carbolithiation of N -alkenyl substituted o -iodoanilines 51 affords enantiomerically enriched 2,4-disubstituted tetrahydroquinolines 52 and 53 by using (−)-sparteine ( L1 ) as chiral ligand [52]. An amide group is also required to favor the cyclization, and also has an important effect in both the diastereoselectivity and the enantioselectivity.…”
Section: Reviewmentioning
confidence: 99%
“…Among the several variants for synthesis of quinolines, the palladium-mediated cyclization processes [ 26 , 27 , 28 , 29 ] and, in particular, the intramolecular Mizoroki–Heck reaction [ 30 , 31 , 32 , 33 ] stand out as valuable synthetic protocols. In our research program on quinoline synthesis [ 34 , 35 , 36 ], we have reported [ 37 ] an effective protocol for the synthesis of 2-substituted 4-alkylidenetetrahydroquinoline derivatives, which employs a 6- exo -trig Mizoroki–Heck cyclization of N -alkenyl-substituted 2-haloanilines ( Figure 3 a). When non-substituted alkenes are used, the reaction can be directed towards the formation of an exocyclic or endocyclic carbon-carbon double bond, while 4-alkylidenetehtrahydroquinolines are obtained regioselectively with substituted alkenes.…”
Section: Introductionmentioning
confidence: 99%